2018
DOI: 10.1589/jpts.30.140
|View full text |Cite
|
Sign up to set email alerts
|

Extension of knee immobilization delays recovery of histological damages in the anterior cruciate ligament insertion and articular cartilage in rabbits

Abstract: [Purpose] To investigate the influence of knee immobilization period on recovery of histological damages in the anterior cruciate ligament (ACL) insertion and articular cartilage in rabbits. This knowledge is important for determining the appropriate rehabilitation approach for patients with ligament injuries, fracture, disuse atrophy, and degenerative joint disease. [Materials and Methods] Forty-eight male Japanese white rabbits were divided equally into the remobilization and control groups. The remobilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Complete immobilization of knee joints has been noted to be beneficial for up to 2 weeks post-surgery by decreasing rate of apoptosis and increasing rate of proliferation. 25 However, immobilization of longer than 2 weeks or shorter than 1 week has been noted to cause further damage within the joint by increasing rate of apoptosis, decreasing rate of proliferation, and decreasing glycosaminoglycan content. 26 Since the timeline of cartilage damage to PTOA is not fully understood, it is unclear if movement of an injured joint may further damage chondrocytes.…”
mentioning
confidence: 99%
“…Complete immobilization of knee joints has been noted to be beneficial for up to 2 weeks post-surgery by decreasing rate of apoptosis and increasing rate of proliferation. 25 However, immobilization of longer than 2 weeks or shorter than 1 week has been noted to cause further damage within the joint by increasing rate of apoptosis, decreasing rate of proliferation, and decreasing glycosaminoglycan content. 26 Since the timeline of cartilage damage to PTOA is not fully understood, it is unclear if movement of an injured joint may further damage chondrocytes.…”
mentioning
confidence: 99%
“…A plethora of in vitro and in vivo studies show joint cartilage atrophy after long-term mechanical unloading (i.e., joint immobilization) [15][16][17][18][19][20][21][22][23][24] . For example, in a case study involving ten healthy young individuals (4 males and 6 females), with no history of KOA requiring 6 to 8 weeks of non-weight bearing for injuries affecting the distal lower extremity, the axial mechanical unloading of the joint resulted in increased magnetic resonance imaging (MRI) parameters, T1rho and T2 relaxation times, of the knee articular cartilage that resembled signs of KOA.…”
Section: Background and Summarymentioning
confidence: 99%
“…The changes within cells and cartilage matrix had the degenerative-dystrophic character. Though, Mutsuzaki et al showed that knee immobilization after anterior cruciate ligament insertion leads to chondrocyte apoptosis activation as well as to thinning of cartilage layers [21]. This is the first report about the effect of femur and tibia extra-articular injury on the structure of the knee articular cartilage.…”
Section: Discussionmentioning
confidence: 95%